Recurrent severe cutaneous reaction to fluoroquinolones and rifampicin in a human immunodeficiency virus-positive patient with disseminated tuberculosis: A rare case report - Divya Chamariya; Taru Garg; Hitesh Verma; Lalit Kumar Gupta (Indian Journal of Pharmacology, 2026)
Abstract: We report a 47-year-old human immunodeficiency virus-positive male with disseminated tuberculosis who developed recurrent maculopapular eruptions with mucosal involvement following exposure to multiple drugs, including diclofenac, rifampicin, and fluoroquinolones. Sequential drug rechallenge strongly implicated fluoroquinolones and rifampicin. He was successfully managed with systemic corticosteroids, intravenous immunoglobulin, and careful sequential reintroduction of nonculprit anti-tubercular therapy drugs. This case highlights the importance of drug reintroduction and cautious use of fluoroquinolones and rifampicin in immunocompromised patients.